2018
DOI: 10.1111/jdv.15102
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral imaging system in the delineation of Ill‐defined basal cell carcinomas: a pilot study

Abstract: HIS has the potential to be an easy and fast aid in the preoperative delineation of ill-defined BCCs, but further adjustment and larger studies are warranted for an optimal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…We found that BCCs within the basosquamous, metatypical, micronodular, infiltrative, morpheaform and sclerosing subtypes were more likely to have LSE (Table ). Our findings are consistent with past literature, which presents these subtypes as more histologically aggressive . As such, it is important for clinicians to remember these subtypes as being more aggressive, since they exhibit more LSE within their particular BCC subtype.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that BCCs within the basosquamous, metatypical, micronodular, infiltrative, morpheaform and sclerosing subtypes were more likely to have LSE (Table ). Our findings are consistent with past literature, which presents these subtypes as more histologically aggressive . As such, it is important for clinicians to remember these subtypes as being more aggressive, since they exhibit more LSE within their particular BCC subtype.…”
Section: Discussionsupporting
confidence: 92%
“…Both univariate and multivariate analyses suggest BCCs presenting in Zones 1 and 2 are more likely to have LSE than BCCs in Zone 3. BCCs are typically located on the most sun‐exposed areas of the body, particularly the head and neck . Several retrospective studies found the central face to be a high‐risk location for the development of BCC – the nose, cheek, forehead, scalp, periauricular and periorbital areas were the most prominent and sun‐damaged areas .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macroscopic HSI has been thoroughly employed in tissue classification [8][9][10][11][12][13], lesion segmentation [14,15], and quantification of detectable chromophores [16,17], among others (for further discussion on the capabilities of HSI as a clinical technique, please refer to reviews [17], [18], [19] and [20]). In the field of dermatology, multispectral digital skin lesion analysis (MSDSLA) devices are capable of detecting inflammation [21], segmenting and differentiating between malignant and benign melanocytic and non-melanocytic lesions [22][23][24][25][26][27][28][29]. Chromophores present in melanocytic lesions have been evaluated in large spectroscopic studies as well [30].…”
Section: Introductionmentioning
confidence: 99%